Study of Salmonella spp. from Cage Papers Belonging to Pet Birds in an Argentinean Canary Breeder Championship - Bueno, Dante Javier; Rodríguez, Francisco I.; Machado, Luciana C.; Soria, Mario; Procura, Francisco; Gómez, Silvana C.; Hoffmann, Teresa Magali; Alcain, Andrea; Caffer, María Inés; Latorre, Juan D.; Quintar, Javier O. (MDPI, 2024)
Birds, including canaries and other birds, have become increasingly popular as pets. Bird fairs, where breeders gather and show their production in a championship setting, present a setting for possible Salmonella spp. contamination and transmission. Therefore, this study estimated the rate of Salmonella spp. isolation from cage papers, located in the bottom of cages of exotic pet birds, including canaries. Collected Salmonella isolates were used to determine the antimicrobial resistance profile to 52 antibiotics and 17 commercial disinfectants, based on pure or a mixture of acids, alcohols, aldehydes, alkalis, halogens, peroxygen, and quaternary ammonium compounds. The samples consisted of 774 cage papers taken in the 2015 Argentinean canary breeder championship, pooling three cage papers into one sterile sampling bag. Only one pool of the cage papers was positive for Salmonella spp. (0.4%), which belonged to the sample from three frill canary cages. Two strains of Salmonella serotype Glostrup were isolated, which were only resistant to sulfonamides and erythromycin and sensitive to alkali-based product PL301 AS. Although the rate of Salmonella spp. isolation from cage papers in an Argentinean canary breeder championship is low, it should not be discounted because Salmonella ser. Glostrup can be a source of human Salmonella outbreaks and they show high resistance to disinfecting products.